Influence of melatonin on the physiology and the conduct of ungulates - Correa, Lina María (2017)
The physiological and behavioral changes in ungulates are an adaptive response to environmental changes. The endogenous biological clock allows each individual animal to produce these changes in response to environmental fluctuations. The daylight is the main factor that modulates this process, and its changes are reflected by variations in the melatonin concentrations. This review describes the translation of the light signal into changes in hormone concentration in ungulates. Then mechanism as photoperiod modifies physiological processes such as reproduction, and physical and behavioral aspects are presented. Finally this review discusses the relationship of genes in the development of biological clock. The understanding of the mechanisms that modulate the physiological and behavioral changes in ungulates facilitates handling of animals, especially those species where management is the key factor to productive and/or conservation captivity systems.